2023
DOI: 10.1101/2023.05.07.539762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution spatial multi-omics reveals cell-type specific nuclear compartments

Yodai Takei,
Yujing Yang,
Jonathan White
et al.

Abstract: The mammalian nucleus is compartmentalized by diverse subnuclear structures. These subnuclear structures, marked by nuclear bodies and histone modifications, are often cell-type specific and affect gene regulation and 3D genome organization. Understanding nuclear organization requires identifying the molecular constituents of subnuclear structures and mapping their associations with specific genomic loci in individual cells, within complex tissues. Here, we introduce two-layer DNA seqFISH+, which allows simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…For example, both granule cells and Purkinje cells lack neuron-specific non-CpG DNA methylation ( 13 ), revealing that non-CpG methylation was neither required for our previously discovered neuron-specific radial genome movement ( 5 )—which we observed in both cell types (fig. S27) ( 36 )—nor required for suppressing ultra–long-range contacts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both granule cells and Purkinje cells lack neuron-specific non-CpG DNA methylation ( 13 ), revealing that non-CpG methylation was neither required for our previously discovered neuron-specific radial genome movement ( 5 )—which we observed in both cell types (fig. S27) ( 36 )—nor required for suppressing ultra–long-range contacts.…”
Section: Discussionmentioning
confidence: 99%
“…S32a, Supplementary Material online). Leveraging high-resolution genome-wide seqFISH+ imaging data in mESCs ( Takei et al 2023 ), we also observed a significant shorter mean spatial distance for retrocopy–parent pairs identified as colocalized by Hi-C in comparison with noncolocalized pairs ( P = 6.1 × 10 −94 ; supplementary fig. S33a, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 64%
“…S32A). Leveraging high-resolution genome-wide seqFISH+ imaging data in mESCs (Takei et al 2023), we also observed a significant shorter mean spatial distance for retrocopy-parent pairs identified as colocalized by Hi-C in comparison with noncolocalized pairs (p = 6.1 × 10 -94 , supplementary fig. S33A).…”
Section: Colocalized Retrocopies Are More Likely To Be Functional And...mentioning
confidence: 66%
“…For two-layer seqFISH+ data in mESC (Takei et al 2023), we downloaded the physical coordinates (x, y, and z) of 100,049 genomic loci at 25-kb resolution in 1,076 cells from Zenodo (doi: 10.5281/zenodo.7693825). The spatial distance between any pair of loci binned at 200-kb resolution was calculated using the scripts provided by the authors (https://github.com/CaiGroup/dna-seqfish-plus-multi-omics).…”
Section: Methodsmentioning
confidence: 99%